(untitled) (PANGEEA, 2025)
Sound pollution is a growing environmental health issue. This study measures noise levels at the 1 December 1918 University of Alba Iulia using a class-1 sound level meter, identifies main noise sources, and assesses effects on students and staff, proposing mitigation measures to improve learning and resting conditions.